+0  
 
0
127
1
avatar+3650 

Help 23,24

NotSoSmart  May 15, 2018
 #1
avatar+816 
+2

23)

y=x^2 -8x +18

 

y -18 = x^2-8x

 

y-18 +16  = (x-8x+16)

 

y-2 = (x-4)^2

 

vertex(4,2)

 

Because (x-4)^2 has a coefficient of 1, and (y-k)= 1/4p(x-h)^2, p's value is 1/4.

 

Because has a positive coefficient, the parabola is pointing upwards, so the focus is above the vertex. 

 

Focus(4, 2.25)

 

Directrix( y = 1.75)

 

24).

(x-2)^2 + (y-1)^2 = 16 

becomes 

(x-2+4)^2 + (y+1-6)^2 = 16

cleaned up 

(x+2)^2 + (y-5)^2 = 16

Landry  May 15, 2018

41 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.